A Study on Human Rights in India: The Evolution and Impact of Human Rights in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Human rights are moral rights and they are based on ethical reasons. Human rights conceived without the fundamental right of freedom of thinking and expression which respects the dignity and uniqueness of all men and women. It was recognized that mankind cannot develop without human rights. For this reason, in the last 60 years individual human beings have progressively gained more human rights and responsibilities, and we have seen loss of human ideals and rights during and at the time of the two World wars.